A Review of Parametric and AMMI Models for Genotype x Environment (G x E) Interaction in Mulberry - Tejaswini A S; Shravanilakshmi V; Nikita Kankanawadi; Veenita M K; Kaveri Aramani; Vinayak Madarakhandi (Archives of Current Research International, 2025)
Mulberry (Morus spp.) is a key perennial crop cultivated primarily for its leaves, which serve as the sole food for silkworms. The productivity of mulberry varies widely across different agro-climatic environments due to Genotype x Environment (G x E) interactions, posing a challenge for stable varietal development. In the present review, an attempt has been made to find out the parametric models for the stability of mulberry genotypes across seasons. The importance of G x E interaction and the use of various stability models such as Finlay & Wilkinson, Eberhart & Russell, Perkins & Jinks, Freeman & Perkins and AMMI models in evaluating mulberry genotypes. These models help identify high-yielding and stable genotypes adaptable to diverse environments, improving selection efficiency. Understanding adaptability and stability is crucial for breeding programs aimed at enhancing leaf yield, quality and stress tolerance. The integration of statistical models and multi-environment trials facilitates the development of mulberry varieties suited for large-scale sericulture under varying climatic conditions. The study approach ultimately supports sustainable mulberry cultivation and silkworm rearing.